2019
DOI: 10.1177/1744629519874214
|View full text |Cite
|
Sign up to set email alerts
|

Internet use for family carers of people with intellectual disabilities: A literature review and thematic synthesis

Abstract: Being a family carer can be rewarding but can also lead to mental and physical exhaustion as well as feelings of social exclusion and isolation. Research has shown that the use of the Internet and online forums can provide an immediate place to find information and reassurance and that forum use can be an empathetic place to share experiences and seek emotional support. This article details a systematic literature search of research on carers of people with intellectual disabilities and/or autism using the Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Carers in other studies have made similar comments around this format ( Blom et al, 2015 ; Dam et al, 2017 ). Community hesitancy around privacy online is present in other peer support research, where users discuss the importance of maintaining their anonymity ( Caton et al, 2019 ; Chan et al, 2016 ; Hanna & Gough, 2018 ). In addition to privacy concerns, carers in the literature perceive online designs as lacking trust, quality control, and targeted information ( Gibson et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Carers in other studies have made similar comments around this format ( Blom et al, 2015 ; Dam et al, 2017 ). Community hesitancy around privacy online is present in other peer support research, where users discuss the importance of maintaining their anonymity ( Caton et al, 2019 ; Chan et al, 2016 ; Hanna & Gough, 2018 ). In addition to privacy concerns, carers in the literature perceive online designs as lacking trust, quality control, and targeted information ( Gibson et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the participants in this study frequently searched for information on the internet, similar to other parents from around the world, and used it to understand their child's disease (Alsem et al, 2017). In addition, the internet was used to form emotional bonds with parents of children with similar diseases and to obtain information on various treatments and activities for children through parental communities (Caton et al, 2019; Nicholl et al, 2017). Parents were less satisfied with the results from an internet search, and they preferred information received from parent communities.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that families who received education around future planning and supports are more likely to engage in creating LTC plans (Burke et al, 2018). And while a general internet search for LTC generates multiple potential resources, a systematic review of internet use among family caregivers of people with intellectual or developmental disabilities found that (1) caregivers find the volume of information on the internet overwhelming; (2) internet‐based searches are challenging and time‐consuming to identify relevant information; and (3) misinformation or negativity is problematic (Caton et al, 2019). Consequently, integrated and curated LTC planning tools, such as The Arc's Center for Future Planning (The Arc's Center for Future Planning, n.d.) and University of Northwestern's Plan Your Lifespan (Lindquist et al, 2017; Ramirez‐Zohfeld et al, 2021), are valuable.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, few evidence‐based interventions exist to support LTC planning specifically for people with intellectual or developmental disabilities and/or their caregivers: a 2020 systematic review found only four high‐quality studies assessing approaches to future care planning for adults with intellectual or developmental disabilities and their family caregivers (Brennan et al, 2020). For most families, usual care consists of families navigating disability social services websites independently (Caton et al, 2019; Hostetter & Klein, 2018; McLean et al, 2021), being introduced to LTC services as part of transition planning of a graduating student's individualised education plan (Grigal et al, 2011; Powers et al, 2005; Shogren & Plotner, 2012), or being referred to case management services through a health system or agency. Although case management programs may lead to enhanced planning for the future and increased access to services (Bigby et al, 2002), these approaches are limited by accessibility.…”
Section: Introductionmentioning
confidence: 99%